Fluoride prevalence in groundwater around a fluorite mining area in the flood plain of the River Swat, Pakistan - Rashid, Abdur; Guan, Dong-Xing; Farooqi, Abida; Khan, Sardar; Zahir, Salman; Jehan, Shah; Khattak, Seema Anjum; Khan, Muhammad Sufaid [UNESP]; Khan, Raees (Elsevier, 2018)
This study investigated the fluoride (F−) concentrations and physicochemical parameters of the groundwater in a fluorite mining area of the flood plain region of the River Swat, with particular emphasis on the fate and distribution of F− and the hydrogeochemistry. To better understand the groundwater hydrochemical profile and F− enrichment, groundwater samples (n = 53) were collected from shallow (24–40 m), mid-depth (48–65 m) and deep (85–120 m) aquifers, and then analysed using an ion-selective electrode. The lowest F− concentration (0.7 mg/L) was recorded in the deep-aquifer groundwater, while the highest (6.4 mg/L) was recorded in shallow groundwater. Most groundwater samples (62.2%) exceeded the guideline (1.5 mg/L) set by the World Health Organization (WHO); while for individual sources, 73% of shallow-groundwater samples (F− concentration up to 6.4 mg/L), 42% of mid-depth-groundwater samples, and 17% of deep-groundwater samples had F− concentrations that exceeded this permissible limit. Assessment of the overall quality of the groundwater revealed influences of the weathering of granite and gneisses rocks, along with silicate minerals and ion exchange processes. Hydrogeochemical analysis of the groundwater showed that Na+ is the dominant cation and HCO3 − the major anion. The anionic and cationic concentrations across the entire study area increased in the following order: HCO3 > SO4 > Cl > NO3 > F > PO4 and Na > Ca > Mg > K, respectively. Relatively higher F− toxicity levels were associated with the NaHCO3 water type, and the chemical facies were found to change from the CaHCO3 to (Na–HCO3) type in calcium-poor aquifers. Thermodynamic considerations of saturation indices indicated that fluorite minerals play a vital role in the prevalence of fluorosis, while under-saturation revealed that – besides fluorite minerals – other F− minerals that are also present in the region further increase the F− concentrations in the groundwater. Finally, a health risk assessment via Dean's classification method identified that the groundwater with relatively higher F− concentrations is unfit for drinking purposes.
Keywords: Dental fluorosis; Flood plain area; Fluoride bearing minerals; Geochemical modeling; Groundwater; Hydrogeochemistry